2011
DOI: 10.1111/j.1740-0929.2011.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo gene transfer into skeletal muscle of neonatal chicks by electroporation

Abstract: Chicks (Gallus gallus domesticus) show considerable growth of skeletal muscle during the neonatal period. The in vivo gene transfer method is useful for studying gene function and can be employed to elucidate the molecular mechanisms of skeletal muscle growth in chicks. We evaluated the following conditions for gene transfer to the skeletal muscle of neonatal chicks by electroporation: (i) voltage; (ii) age of the chick; (iii) plasmid DNA injected amount; and (iv) duration of gene expression. The results obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The highly vascularized and stable nature of the skeletal muscle opens up opportunities for introducing gene-transfer agents into the systemic circulation for the treatment of human diseases distant from the site of muscle treatment. 28 For example, Liu et al 29 reported that expression of NEP in skeletal muscle using an adeno-associated virus (AAV) reduced Ab in a transgenic mouse model of AD. However, this previous study only measured NEP expression in injected local skeletal muscle but not in brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The highly vascularized and stable nature of the skeletal muscle opens up opportunities for introducing gene-transfer agents into the systemic circulation for the treatment of human diseases distant from the site of muscle treatment. 28 For example, Liu et al 29 reported that expression of NEP in skeletal muscle using an adeno-associated virus (AAV) reduced Ab in a transgenic mouse model of AD. However, this previous study only measured NEP expression in injected local skeletal muscle but not in brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These findings demonstrate that peripheral expression of NEP, and likely other peptidases, represents an alternative to direct administration into the brain and illustrates the potential for using NEP expression in muscle for the prevention and treatment of AD (Liu et al, ). In particular, skeletal muscle cells, which are postmitotic and have longevity, allow the stable expression of injected plasmid DNA and can be safely and easily manipulated (Ijiri et al, ). Thus, this may become a promising strategy in the medical treatment of AD.…”
Section: Viral Vector‐mediated Nep Gene Therapy For Admentioning
confidence: 99%